Effect of COVID-19 on the Performance of Sectoral Indices Listed on the Indonesia Stock Exchange in 2019-2020 - Novi Puji Lestari; Venus Kusumawardhana (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to: (1) examine and analyze the impact of the pandemic on the development of the Capital Market JCI in Indonesia; (2) analyze the influence of the Covid-19 externality on the dynamics of the development of the Capital Market sectoral index in Indonesia. The research uses a case study method with a quantitative analysis approach using sectoral stock index history data with purposive sampling technique. The research population is 9 sectoral indices listed on the Indonesia Stock Exchange. The research period is November 2019-December 2020 which is analyzed using the Chartnexus analysis tool based on the performance of the stock sector index. The results of this study can be used as a reference for potential investors in choosing and investing in stocks that are included in sectoral indices whose market recovery is faster during the pandemic.